Analysis of the Machining Quality of Liner Plates Using Shaping, Turning, and Milling Methods in Shipbuilding Construction - HARI SUSANTO HARI; Tri Agung Kristiyono (Politeknik Negeri Madura, 2025)
Liner plate functions as a vibration damping pad between the foundation and heavy equipment such as windlass and main engine in ship construction. Dimensional accuracy and surface roughness are very important for the liner plate to produce optimal contact area. This study compares the quality of liner plate machining results using three methods: shaping, CNC milling, and turning. Evaluation parameters include dimensional precision (thickness), surface roughness (Ra), and production time efficiency. The results show that CNC milling provides the best quality in terms of precision and roughness, although it takes longer to process. The lathe shows balanced results between time efficiency and quality. The scrap machine is suitable for the initial stage of work but is less ideal for precise final results. This study can be a reference in selecting the optimal liner plate machining method in ship construction. Keywords: liner plate; machining; milling; shaping; turning.